Contact Geometry Adaptation in Fretting Wear: A Constructive Review - Argatov, Ivan; Chai, Young Suck (Frontiers in Mechanical Engineering, 2020)
Fretting is a special type of wear, which appears at the contact interface between two solids subjected to constant normal load and periodic tangential forces. Although most studies on fretting have been executed experimentally, some approaches for simulating fretting wear have also been introduced during the last decades. In particular, fretting wear analysis is concerned with the evolution of the surface profiles of the contacting bodies due to wear, and its modeling was executed using numerical, finite-element, semi-analytical and analytical methods, including the method of dimensionality reduction. In the present review we discuss recent analytical results on fretting wear contact geometry adaptation.